A Decade of Progress on Solid‐State Electrolytes for Secondary Batteries: Advances and Contributions. (16th April 2021) - Sheng, Ouwei; Jin, Chengbin; Ding, Xufen; Liu, Tiefeng; Wan, Yuehua; Liu, Yujing; Nai, Jianwei; Wang, Yao; Liu, Chuntai; Tao, Xinyong
Abstract: Compared with conventional liquid batteries, all‐solid‐state batteries (ASSBs) show great promise for enabling higher safety in electric vehicles without compromising operational durability and range. As a key component of ASSBs, solid‐state electrolytes (SSEs) need high ionic conductivity and favorable interfacial compatibility between electrodes and SSEs. In the recent decade, numerous efforts have been devoted to SSE advancement and fruitful achievements have been made, particularly regarding metal anode‐oriented SSEs with high energy density. This review focuses on the historical process of SSEs employed in ASSBs. The new understanding and origins for the enhanced ionic conductivity and mechanical properties of SSEs are first summarized. As to the cathode/SSE interface, its decomposition mechanism and modification strategies are analyzed. As to the interfacial issues of SSEs with anodes, the mechanisms of dendrite formation and penetration into the SSEs are discussed in detail. Additionally, assisted by a library of big data sources, contributions are systematically highlighted from different countries, institutions, and corresponding authors to significantly advance SSE progress, and certain insights are provided into the underlying relationships between various items in a collective manner. Finally, current challenges and potential strategies are identified for the future development of SSEs in ASSBs. Abstract : By illustrating the correlation between performance improvement/failure of solid state electrolytes (SSEs) and microscale material design, this review aims to provide a comprehensive evolution view and an iterative historical perspective of the SSEs over the past 10 years.